An external perspective on CSR: What matters and what does not?. (14th August 2017) - Vashchenko, Marina
Abstract: The paper aims at investigating external factors influencing organizational corporate social responsibility (CSR)‐related decision making. Two theoretical perspectives—stakeholder theory and institutional theory—have been applied to compile a list of external factors that might affect a company's CSR choices. As a result, a framework built on the government‐related, society‐related, and business‐related groups of external factors is being suggested. This framework is used in the paper to answer (a) to what extent do different external factors influence CSR‐related decisions in large Danish companies and (b) how has that influence changed over the years. The research takes a qualitative approach and is designed as a multiple‐case study. Empirically, the paper relies on data collected from semi‐structured interviews with CSR specialists and managers and presents a dynamic perspective on the pressure exercised by the external factors on CSR decisions and choices.